Corollaries of Point Spread Function with Asymmetric Apodization - Naresh Kumar Reddy Andra; Udaya Laxmi Sriperumbudur; Karuna Sagar Dasari (International Journal of Optics)
Primary energy based corollaries of point spread function with asymmetric apodization using complex pupil function have been studied in the case of three-zone aperture. Merit function like semicircled energy factor, excluded semicircled energy, and displaced semicircled energy were analyzed with respect to Airy case in terms of phase and amplitude apodization. Analytical results have been presented for the optimum parameters of phase and amplitude asymmetric apodization.